Efficacy and mechanism of acupuncture in animal models of depressive-like behaviors: a systematic review and meta-analysis - Huang, Yingjie; Chen, Weiping; Li, Xingfu; Tan, Tian; Wang, Tunyi; Qiu, Shishi; Li, Guangyao; Yang, Cong; Li, Min; Duan, Lining (Frontiers in Neuroscience, 2024)
Background Many studies have investigated the efficacy of acupuncture in treating depression, but the mechanism of acupuncture for depression is still controversial and there is a lack of meta-analysis of mechanisms. Consequently, we investigated acupuncture’s efficacy and mechanism of depression. Methods We searched the Cochrane Library, PubMed, EMBASE, Web of Science. The SYRCLE Risk of Bias Tool was used to assess bias risk. Meta-analysis was performed using Stata 15.0 for indicators of depression mechanisms, body weight and behavioral tests. Results A total of 22 studies with 497 animals with depressive-like behaviors were included. Meta-analysis showed that acupuncture significantly increased BDNF [SMD = 2.40, 95% CI (1.33, 3.46); I2 = 86.6%], 5-HT [SMD = 2.28, 95% CI (1.08, 3.47); I2 = 87.7%] compared to the control group (p < 0.05), and significantly reduced IL-1β [SMD = −2.33, 95% CI (−3.43, −1.23); I2 = 69.6%], CORT [SMD = −2.81, 95% CI (−4.74, −0.87); I2 = 86.8%] (p < 0.05). Acupuncture improved body weight [SMD = 1.35, 95% CI (0.58, 2.11); I2 = 84.5%], forced swimming test [SMD = −1.89, 95% CI (−2.55, −1.24); I2 = 76.3%], open field test (crossing number [SMD = 3.08, 95% CI (1.98, 4.17); I2 = 86.7%], rearing number [SMD = 2.53, 95% CI (1.49, 3.57); I2 = 87.0%]) (p < 0.05) compared to the control group. Conclusion Acupuncture may treat animals of depressive-like behaviors by regulating neurotrophic factors, neurotransmitters, inflammatory cytokines, neuroendocrine system. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023403318, identifier (CRD42023403318).